Three-Dimensional Ordered Porous Carbon for Energy Conversion and Storage Applications - Feng, Jinxiu; Zheng, Dong; Gao, Xinlong; Que, Wenbin; Shi, Wenhui; Liu, Wenxian; Wu, Fangfang; Cao, Xiehong (Frontiers in Energy Research, 2020)
The performance of energy storage devices is highly related to the properties of electrode materials, such as components, morphology, configurations and so on. As a typical hierarchical carbon material, three-dimensional ordered porous carbon (3D-OPC) has unique characteristics of low cost, large specific surface area, highly ordered channels, and high electronic and ionic conductivity, which shows great potential in energy storage and conversion applications. In this mini review, we summarize various template-assisted preparation methods for 3D-OPC, including hard-, ice- and self-templated approaches, and their applications in electrocatalysis, batteries and supercapacitors. Additionally, the critical roles of vertical channels in 3D-OPC when used as electrodes are also discussed. Finally, the current challenges and future research outlook of 3D-OPC are proposed.